The burden of caring for dementia patients: caregiver reports from a cross-sectional hospital-based study in China. (October 2013) - Mould-Quevedo, Joaquín F; Tang, Boxiong; Harary, Eran; Kurzman, Ricky; Pan, Sharon; Yang, Jiyue; Qiao, Juan
The impact of dementia care on caregivers' professional, personal, emotional and social well-being was measured in a cohort of 1, 387 caregivers in seven regions across mainland China, using a Chinese version of the Zarit Burden Interview (ZBI) and four supplementary questions. Caregivers also estimated costs of care and medical resource utilization. Caregiver burden was generally low to moderate. Dementia care had the greatest impact on caregivers' professional lives, with 25.5% reporting a reduced work schedule in the past month. Lost work time was greater for caregivers of patients with previously diagnosed dementia than for those with newly diagnosed dementia. Average monthly out-of-pocket costs of dementia care exceeded national average monthly incomes of rural and urban residents. These findings highlight the obstacles facing the country with the fastest-growing elderly population in the world.